EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB-P2) DI DESA TIBONA KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA - Muh Yasin Noor (Jurnal Riset Perpajakan: Amnesty, 2020)
The purpose of this study was to study the level of land and building tax (PBB) receipts in Tibona village, Bulukumpa Subdistrict, Bulukumba District, anything that affects the level of acceptance of land and building tax revenue. The type of research used descriptive qualitative where the researcher describes the results of observations and analyzes the data obtained in the field. This Final Project is the result of research conducted from March 6, 2019 to May 6, 2019. After analyzing and discussing the problems, the researcher concluded that the level of effectiveness of land and building tax receipts in Tibona Village, Bulukumpa Subdistrict, Bulukumba District, in terms of compliance levels increased even though it was still quite effective, because there were still many taxpayers who had not paid attention to their obligations and lack of knowledge and understanding in paying taxes, and late billing, in this case, the Bontolanran village government in collecting taxes and lack of human resources (HR).